Spiritual Leadership in Early Intervention Practice - Jo L. McCray (Adult Education Research Conference, 2022)
This study explored integrating the principles of spiritual leadership theory into early intervention therapeutic practice to enhance services provided to children and families. Semi structured interviews served as major sources of data.
Keywords: Education; Counseling; Leadership